SAT0040 Rheumatic diseases in patients with vitiligo: a study on 28 cases. (1st June 2001) - Olivieri, I; Ciancio, G; Padula, A; La Civita, L; Piccirillo, A; Ricciuti, F; Cantini, F; Niccoli, L; Salvarani, C
Abstract : Background: Recently, we have demonstrated in a case-control study that vitiligo and spondyloarthropathy (SpA) do not coexist by chance in the same patient. 1 Of the 234 patients with SpA seen in the study period 8 (3.4%) were found to be suffering from type A vitiligo. On the contrary, among the 468 control patients only 5 (1.06%) had type A vitiligo. The difference was statistically significant (p < 0.05). Objectives: To establish the reasons for the rheumatological consultation in consecutive patients with vitiligo seen for the first time in our department. Methods: All patients that showed visible type A vitiligo in peri-orificial sites (around mouth, nose, eyes) and/or over the extensor surfaces of hands and wrists, seen for the first time in our department from January 1999 to 31 December 2000, were evaluated clinically. X-ray and laboratory examinations were performed when necessary. Results: Twenty-eight patients with visible vitiligo were seen. Of these, 4 had inflammatory rheumatic diseases associated with vitiligo (2 elderly onset undifferentiated SpA, 2 psoriatic arthritis, 1 rheumatoid arthritis together with lupus profundus). Five patients had inflammatory rheumatic diseases with dubious relationships with vitiligo (3 polymyalgia-like syndrome, 1 seronegative chronic polyarthritis, 1 severe peripheral enthesitis). The remaining 17 patients had vitiligo unrelated rheumatic diseases including osteoarthritis, mechanical low back pain, herniated disc, spondylolisthesis, condrocalcinosis, rotator cuff tendinitis, olecranic bursitis and trigger finger. Seven out of the 28 patients had diseases of the thyroid gland and 1 alopecia areata. Conclusion: The results of the present study confirm the association between vitiligo and SpA. Some patients with vitiligo have undifferentiated inflammatory rheumatic diseases, which need to be followed up. Reference: Padula A, et al . Association between vitiligo and spondyloarthropathy. J Rheumatol. 2001;28, in press